Changing player behaviour in sport during the COVID-19 pandemic: Shake on it? - McKenna, J.; Backhouse, S. H.; Phillips, G.; Jones, B. (South African Journal of Sports Medicine, 2020)
To prevent the spread of infection during matches and training activities is a major challenge facing all sports returning from the enforced COVID-19 shutdown. During training and matches, rugby league players make contact with others which can result in SARS-CoV-2 virus transmission. While these interactions characterise the appeal of the game, a number of them can be avoided, including shaking hands and conversing after the match. This paper presents a framework underpinned by behavioural science (capability, opportunity, motivation and behaviour model, COM-B) to support stakeholders in helping players adopt new social distance norms and behaviours. This framework helps to ensure the players have the capability, opportunity, and motivation to adopt new COVID-19 risk minimising behaviours, which they will need to commit to 100%.